2013
DOI: 10.1371/journal.pone.0084059
|View full text |Cite
|
Sign up to set email alerts
|

CHRNA7 Polymorphisms and Response to Cholinesterase Inhibitors in Alzheimer's Disease

Abstract: Background CHRNA7 encodes the α7 nicotinic acetylcholine receptor subunit, which is important to Alzheimer's disease (AD) pathogenesis and cholinergic neurotransmission. Previously, CHRNA7 polymorphisms have not been related to cholinesterase inhibitors (ChEI) response.MethodsMild to moderate AD patients received ChEIs were recruited from the neurology clinics of three teaching hospitals from 2007 to 2010 (n = 204). Nine haplotype-tagging single nucleotide polymorphisms of CHRNA7 were genotyped. Cognitive resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…Acetylcholinesterase inhibitors (AEI), such as galantamine are frequently utilized for treatment of AD (Taylor, 1998). Women with AD carrying the polymorphism rs8024987 in intron 2 of CHRNA7 show improved cognitive symptoms with AEI (Weng et al, 2013). …”
Section: 0 Genetics Of Chrna7 and Chrfam7a In Mental Illnessesmentioning
confidence: 99%
“…Acetylcholinesterase inhibitors (AEI), such as galantamine are frequently utilized for treatment of AD (Taylor, 1998). Women with AD carrying the polymorphism rs8024987 in intron 2 of CHRNA7 show improved cognitive symptoms with AEI (Weng et al, 2013). …”
Section: 0 Genetics Of Chrna7 and Chrfam7a In Mental Illnessesmentioning
confidence: 99%
“…Furthermore, the stimulation of postsynaptic α7nAChR increases calcium influx and activates the intracellular signal transduction pathway, conferring neuroprotective effect by protecting neurons against Aβ toxicity 7 . In addition to disease prediction, our previous work has found that CHRNA7 polymorphisms may predict cognitive response to cholinesterase inhibitors and serve as a pharmacogenomic marker in LOAD treatment 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The CHRNA7 gene is reported to encode α7 nAChR, one of the major nAChR subunits in the central nervous system (CNS), on chromosome 15q14 . In a retrospective study conducted in 233 patients with mild-to-moderate AD, the ratio of responders to non-responders with galantamine treatment was significantly higher in women with the SNP2 of CHRNA7 rs8024987 compared with female non-carriers (p<0.01) [ 80 ]. A similar difference was not observed in patients treated with other ChEIs, suggesting the involvement of the APL effect of galantamine through α7nAChR.…”
Section: Factors Affecting Clinical Response To Cheismentioning
confidence: 99%